Assessing actually-existing trajectories of EU politicisation. Issue 1 (2nd January 2016) - de Wilde, Pieter; Lord, Christopher
Abstract: Theoretical debate about the effects of politicisation on the democratic legitimacy of the European Union has tended to focus on the potential of conflict between European political parties or member state governments. At the same time, empirical sociological studies demonstrate that controversy about Europe continues to unfold primarily within national public spheres. There is as yet no genuine Europe-wide party system or public debate. This reveals a gap between the normative theoretical assessment of EU politicisation and empirical sociological analysis of this phenomenon. To reconcile this discrepancy, this paper develops three actually-existing trajectories of politicisation: the remote conflict, the international conflict and the domestic conflict. Each trajectory carries unique challenges and opportunities to the democratic legitimacy of the Union. It is argued that the domestic conflict trajectory is most promising from a normative democratic perspective. Paradoxically, this does not necessarily imply a renationalisation of the EU.